Peranan Pembimbing Kemasyarakatan Dalam Sistem Peradilan Pidana Anak di Wilayah Hukum Balai Pemasyarakatan Kelas II Kupang - Maria Sonia Savike Pinto; Orpa G. Manuain; Debi F. Ng. Fallo (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Community Advisors are professional officers who work under the Ministry of Law and Human Rights, especially in the Directorate General of Corrections. They are in charge of providing guidance, counseling, and assistance to inmates and correctional clients, including children who are facing the law. The Roles and Responsibilities of Community Advisors are: legal and social assistance, rehabilitation and reintegration, individual and family counseling, supervision and evaluation, coordination with relevant institutions, reports and documentation. Community guidance has a central role in ensuring that children involved in the criminal justice system receive the support they need to reintegrate properly into society. The purpose of this study is to find out what the role of community guidance is and what are the obstacles experienced by community supervisors in handling children who are facing the law. The research method used is an empirical juridical research The results of the study show that: (1) The role of community supervisors is very significant in supporting the implementation of SPPA in Bapas Class II Kupang. They not only act as facilitators in the rehabilitation process, but also as mentors and supporters for children in the criminal justice system. Community counselors are actively involved in developing rehabilitation programs that are tailored to the individual needs of children, providing counseling services, and assisting in the formation of social skills and life skills necessary for reintegration into society. (2) The main obstacles faced by community advisors include limited resources, such as inadequate budgets, and high workloads due to the number of cases exceeding the capacity of employees handling ABH cases. In addition, the obstacles to coordination with related agencies, including judicial institutions, police, and social services, are also a significant challenge, hindering the implementation of integrated rehabilitation program.